NECESSARY CONDITIONS FOR THERMAL IMAGING EXAMINATION - Jobborov, Baxodir Tulqinjon ugli (Educational Research in Universal Sciences, 2023)
Thermal imaging inspection of buildings and structures is a thermographic method for detecting defects present in building structures. Today, it is the most effective way to diagnose the condition of enclosing and other structures at various stages of their operation, from the moment of commissioning to reconstruction. Its relevance and prevalence is due to the reliability and efficiency of obtaining objective data on the main parameters of structures of various types.